Tarekat-Based Female Leadership in Enhancing Teaching Staff Loyalty at Islamic Boarding Schools - Sunardi Sunardi; Ubaidillah Ubaidillah; Muhammad Fadhlan Refa (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
Mainstream literature on Islamic Boarding School Leadership frequently marginalizes female roles and relies heavily on secular transactional theories to explain employee retention. This study aims to address these gaps by analyzing the Tarekat Shadhiliyya-based model of women's Leadership in enhancing teaching staff loyalty. Employing a qualitative case study approach at Al-Urwatul Wutsqo Islamic Boarding School in Jombang, data were collected through in-depth interviews, participant observations, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal that the female Leadership model represents a unique hybrid synthesis of managerial-professional, maternal-nurturing, and spiritual-Mursyid roles. Through the internalization of Shadhiliyya values, specifically Tawazun (Work-Worship Fusion) and Mahabbah (politics of compassion), the Leadership effectively transforms work motivation from a transactional to a transcendental orientation. Theoretically, this study deconstructs the dominant Social Exchange Theory (SET) by proposing the concept of Covenantal Loyalty. Unlike secular loyalty based on material incentives, Covenantal Loyalty is understood as Khidmah (devotion) and Tabarrukan (seeking blessings), and is thus more resilient and sustainable. This research offers a novel perspective on how spiritual values can serve as an epistemological foundation for modern organizational governance.